An Analysis LexIcal Density of Reading text in SMA Imelda Medan - apryl manurung (JETAL: Journal of English Teaching & Applied Linguistic, 2019)
The objectives of the study was to find out the lexical density for lexical items and the dominant kind of lexical items in reading text of the second grade of SMA IMELDA SWASTA MEDAN. This study was conducted by mixed method.This study was done by analysing ten ( 10 ) reading text from the “Bahasa Inggris “ textbook. The result of analysis showed that : (1) seven texts (7) were categories medium ≥50% lexical density. It meant that the text was easy to understand by students and three (3) texts were low ≤50 % lexical density that means the text was easiest to understand in teaching reading. And there was no high lexical density that found in text, it refers there is no text that include the difficult text for students (2) the dominant kinds of lexical items that found in every text was noun ( 48.0%). It meant noun was more use in every text because noun is easy to include new word. The writer concludes that the textbook are suitable for students. The writer was suggested that the teacher can choose the appropriate teaching reading strategy to improve students’ reading comprehension Keywords: : Lexical Density, Lexical Items, Reading Text, Textbook